Management of Policy Implementation for Determination of Areas for Production Forest Management Wae Bubi Model (Unit X) in Seram Bagian Timur Regency, Maluku Province - Rolobessy, Mike Jurnida; Pattimukay, Hengki V. R. (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
Decree of the Minister of Forestry Number SK.978/Menhut-II/2013 dated 27 December 2013 concerning determination of areas for production forest management wae bubi model (unit x) in Seram Bagian Timur Regency. But they are not given the authority to work in the district because it is based on Law Number 23 of 2014 concerning regional government. Not in the forestry law and its derivative regulations. This is a problem related to the authority in determination of areas for production forest management which lies in management of policy implementation for determination of areas for production forest management wae bubi model (unit x) in Seram Bagian Timur Regency, Maluku Province. This study aims to analyze, reveal and describe, management of policy implementation for determination of areas for production forest management wae bubi model (unit x) in Seram Bagian Timur Regency, Maluku Province. The findings of this study have implications for its optimization and contribute to the improvement and strengthening of management of policy implementation for determination of areas for production forest management wae bubi model (unit x) in Seram Bagian Timur Regency. Theoretically, management of policy implementation for determination of areas for production forest management wae bubi model (unit x) model is explored as a scientifically based concept for the development of public administration science. Practically designing the framework for management of policy implementation for determination of areas for production forest management wae bubi model (unit x) as a follow-up process that has implications for constructive production forest management unit management in Seram Bagian Timur Regency.